Hot corrosion-creep interaction in IN718 under simulated marine environment: Introducing strain-associated-time (SAT) plots for comprehensive understanding. (September 2021) - Mannava, Venkateswara Rao; Koundinya, N.T.B.N.; A., SambasivaRao; Paulose, Neeta; M., Kamaraj; Kottada, Ravi Sankar
Graphical abstract: Highlights: Creep-rupture time of IN718 at 650 °C reduced by ∼90 % due to 3SM(Na2 SO4 +NaCl + NaVO3 ). Vanadic-hot-corrosion and dynamic-embrittlement dominates at 675 and 550 MPa. Strain-associated-time (SAT) and Δtε plots are introduced for creep-hot corrosion. 3SM-attack is less severe at 850 MPa, but increases with decreasing stress. Abstract: Creep-rupture behaviour of IN718 with deposit of 87.5 wt.%Na2 SO4 +5 wt.%NaCl+7.5 wt.%NaVO3 (3SM) in the stress range of 550–850 MPa at 650 °C is investigated. 3SM shortens the creep-rupture time by ≈70–90 %. Comprehensive microstructural analysis suggests that oxygen-induced-dynamic- embrittlement, sulphidation followed by oxidation, and vanadic-hot corrosion operate during creep. Creep-hot corrosion interaction influence on rupture strain is explained by introducing strain-associated-time (SAT) and Δtε plots, for the first time. These plots accompanied by detailed microstructural examination demonstrate that deleterious influence of 3SM increases with decreasing stress. Further, SAT plots and EPMA analysis confirm that oxygen-induced-dynamic-embrittlement commences from ∼9% strain under 3SM at 550 MPa.